Wastewater Treatment in the Diary Industry from Classical Treatment to Promising Technologies An Overview - Al-Tayawi Aws N.; Sisay Elias Jigar; Beszédes Sándor; Kertész Szabolcs (2023)
Water pollution caused by population growth and human activities is a critical problem exacerbated by limited freshwater resources and increasing water demands. Various sectors contribute to water pollution, with the dairy industry being a significant contributor due to the high concentrations of harmful contaminants in dairy wastewater. Traditional treatment methods have been employed, but they have limitations in terms of effectiveness, cost, and environmental impact. In recent years, membrane separation technology (MST) has emerged as a promising alternative for treating dairy wastewater. Membrane processes offer efficient separation, concentration, and purification of dairy wastewater, with benefits such as reduced process steps, minimal impact on product quality, operational flexibility, and lower energy consumption. However, membrane fouling and concentration polarization present major challenges associated with this technique. Therefore, strategies have been implemented to mitigate these phenomena, including pre-treatment prior to MST, coagulation, and adsorption. Recently, 3D printing technology has gained prominence as one of the latest and most notable advancements for addressing these issues. This comprehensive review examines the drawbacks and benefits of conventional methods employed in dairy wastewater treatment and explores the utilization of membrane technology as an alternative to these approaches. Additionally, the latest technologies implemented to mitigate or alleviate the limitations of membrane technology are discussed.
Keywords: Műszaki és technológiai tudományok